Volume 1: Offshore Technology 2008
DOI: 10.1115/omae2008-57525
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Results of Tsunami Bore Forces on Structures

Abstract: A series of experiments has been carried out at the Tsunami Wave Basin (TWB) at Oregon State University (OSU) to determine the effect of tsunami bores on coastal and nearshore structures, especially buildings and bridges. The TWB is equipped with a piston-type wavemaker capable of generating clean solitary waves. The facility was used to model tsunami bores breaking over coastal reefs and their impact on structural components, including columns, walls, and horizontal members, such as building floors and bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This PC was placed 15 cm above the flume bottom. This agreed with the observations made by Nouri et al (2010), Robertson et al (2008), Shafiei et al (2016) and Al-Faesly et al (2012). The pressure magnitude measured through each PC decreased proportionally with the height from the flume bottom measured by the PC, which also agreed with the results of studies by Al-Faesly et al (2012), Palermo et al (2012) and Santo and Robertson (2010).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This PC was placed 15 cm above the flume bottom. This agreed with the observations made by Nouri et al (2010), Robertson et al (2008), Shafiei et al (2016) and Al-Faesly et al (2012). The pressure magnitude measured through each PC decreased proportionally with the height from the flume bottom measured by the PC, which also agreed with the results of studies by Al-Faesly et al (2012), Palermo et al (2012) and Santo and Robertson (2010).…”
Section: Resultssupporting
confidence: 91%
“…However, limited focus has been put on the interaction between a three-dimensional (3D) structure and tsunami, where the structure is not overtopped by the flow, owing to the complexities involved in tsunami bore surrounding a structure (Wijatmiko and Murakami, 2012). Previous investigations were limited to the study of the impact of tsunami on the side wall (parallel to the flow), front wall (perpendicular to the flow) (Chinnarasri et al, 2013; Fujima et al, 2009; Nouri et al, 2010; Palermo et al, 2009, 2012; Robertson et al, 2008) and wharf model (Chen et al, 2016, 2017, 2018; Chock et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Palermo et al [10] described the tsunami-induced force components on nearshore structures and reported that the hydrodynamic and surge components were a function of the instantaneous velocity and water depth. Other studies focused on the experimental testing of tsunami bore loads on rectangular buildings [11], piloti-type buildings [12], walls with overhangs [13] and coastal bridges [14][15][16][17]. Some studies evaluated the effects of different wave forms on coastal decks, including unbroken, breaking and post-breaking waves and bores [14,18], and revealed fundamental differences in the effects caused by the two wave types.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 6 and 7 show the pressure histories applied at different locations of the bridge deck, for a selected solitary wave and bore. Given the inherent variability of wave breaking bore formation and induced forces on structures [32][33][34][35][36], it is critical to ensure that the waves inundating the two decks are identical, before any meaningful comparison can be conducted. The wave heights measured at several gauges have been compared and presented in Section 2 of this paper.…”
Section: Pressures On Girders and Below The Deckmentioning
confidence: 99%